Light‐Regulated Polymerization under Near‐Infrared/Far‐Red Irradiation Catalyzed by Bacteriochlorophyll a. (3rd December 2015) - Shanmugam, Sivaprakash; Xu, Jiangtao; Boyer, Cyrille
Abstract: Photoregulated polymerizations are typically conducted using high‐energy (UV and blue) light, which may lead to undesired side reactions. Furthermore, as the penetration of visible light is rather limited, the range of applications with such wavelengths is likewise limited. We herein report the first living radical polymerization that can be activated and deactivated by irradiation with near‐infrared (NIR) and far‐red light. Bacteriochlorophyll a (Bachl a) was employed as a photoredox catalyst for photoinduced electron transfer/reversible addition–fragmentation chain transfer (PET‐RAFT) polymerization. Well‐defined polymers were thus synthesized within a few hours under NIR ( λ =850 nm) and far‐red ( λ =780 nm) irradiation with excellent control over the molecular weight (Mn /Mw <1.25). Taking advantage of the good penetration of NIR light, we showed that the polymerization also proceeded smoothly when a translucent barrier was placed between light source and reaction vessel.